Locally compact space and continuity - Shitanshu Shekhar Choudhary; Raju Ram Thapa (Bibechana, 2010)
Topological spaces for being T0, T1, T2 and regular space have been discussed. The conditions for a topological space to be locally compact have also been studied. We have found that a continuous function preserves locally compactness.